Effects of Non-nutritive Sucking with Emptied Breasts on Breast-Feeding Performance in Preterm Infants - Tongsiri, Phagamas; Wittayasooporn ๋Jariya; Daramas, Tipawan (Nursing Research and Innovation Journal, 2022)
This quasi-experimental research aimed to investigate the effect of non-nutritive sucking with emptied breasts on breastfeeding performance in preterm infants by comparing the breastfeeding performance between the preterm infants sucking on the emptied breasts and the preterm infants receiving routine nursing care. The breastfeeding performance included breastfeeding behaviors, the amount of milk that the infants can suck in the first 5 minutes, and the transition period from tube feeding to breastfeeding. The samples in this study were 46 postpartum mothers, and preterm infants admitted to a tertiary hospital in the northeast region of Thailand. They were selected by purposive sampling based on the inclusion criteria. The motherpreterm infant dyads were equally divided into two groups: 23 dyads were in the control group,and the other 23 dyads were in the experimental group. The experiment consisted of sucking emptied breasts three times a day for 10 minutes for 10 days. When the infants had the postconceptional age of 34 weeks and the pediatrician allowed them to begin breastfeeding, the infants were breastfed. The data were recorded in the breastfeeding performance assessment form.Data were analyzed using Mann-Whitney U Test. The results showed that the breastfeeding behavior score and the amount of milk sucked in the first 5 minutes of preterm infants in the experimental group were significantly higher than those in the control group. Additionally, the transition period from tube feeding to breastfeeding of preterm infants in the experimental group was significantly shorter than in the control group. Therefore, health personnel should encourage preterm infants to receive non-nutritive sucking with emptied breasts to promote better breastfeeding performance. Keywords: Preterm infants, Emptied breast sucking, Breastfeeding performance